Eating Animals: The Influence of Food-based Narratives - Gillian Spolarich; Amanda Ruth-McSwain; Lisa K Lundy (Journal of Applied Communications, 2018)
This study examines the prevalence and persuasiveness of popular food-based narratives. Specifically, the book Eating Animals, a detailed critique of the U.S. meat industry, provided the foundation for exploring the influence of food-based narratives. Guided by the theory of narrative persuasion, a qualitative research design was employed to investigate the influence of this contemporary text on reader perceptions and behaviors. The present study incorporated in-depth interviews with individuals that read all or some of the acclaimed food-based narrative Eating Animals. Findings indicate that the popular narrative motivated a range of attitudinal and behavioral changes. Additional themes that emerged relate to cognitive dissonance, conscious consumerism and interpersonal influence over food consumption decisions. Implications of these findings are discussed relevant to both communication practice and future research.
Keywords: Eating Animals; food narratives; narrative persuasion; cognitive dissonance; conscious consumerism